A REVIEW ON ALZHIMER’S DISEASE: PATHOLOGY, MOLECULAR CONDITIONS, MANAGEMNT AND CAUSES - B, Preethi; MOORTHI P, VINYAGA (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Alzheimer’s disease (AD) is a neurodegenerative disorder that starts slowly, progressively leads to death and contributes to about 60-70% cases of dementia. AD is characterized with Senile Plaques (SPs) and neurofibrillary tangles (NFTs) and the major symptoms include problems with language, dis-orientation of words, unable to manage self-care, memory loss and behavioural issues which gradually lead to completely lose bodily functions later. The actual cause for the disease is not known till date. Recent research show distinct paths that closely try to reveal various cytoplasmic, genetic, behavioural, environmental and epigenetic causes that may lead to the development of AD. Most likely all studies target the Senile Plaques, protein fragments called beta-amyloid and Neurofibrillary Tangles, twisted fibres of a protein called tau. Since, the exact causative mechanism is not yet clearly understood, ultimately finding a suitable treatment or management for the disease has also become an ominous challenge for researchers. Â